1985
DOI: 10.1901/jeab.1985.43-407
|View full text |Cite
|
Sign up to set email alerts
|

Incentive Theory: Iv. Magnitude of Reward

Abstract: Incentive theory is successfully applied to data from experiments in which the amount of food reward is varied. This is accomplished by assuming that incentive value is a negatively accelerated function of reward duration. The interaction of the magnitude of a reward with its delay is confirmed, and the causes and implications of this interaction are discussed.Key words: incentive theory, amount of reward, delay of reward, concurrent chained schedules, concurrent schedules, mathematical models, marginal utilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
3

Year Published

1987
1987
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 31 publications
4
63
3
Order By: Relevance
“…Baum (1974) analyzed data from Fantino, Squires, Delbriuck, and Peterson (1972) in which the feeder times were 1.5 s and 6 s and found that the data suggested a relative value of between 1.5 and 3.2 to 1 (see also Killeen, 1985). Epstein (1981) found that the amount of food consumed is an increasing but decelerating function of the duration for which food is made available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baum (1974) analyzed data from Fantino, Squires, Delbriuck, and Peterson (1972) in which the feeder times were 1.5 s and 6 s and found that the data suggested a relative value of between 1.5 and 3.2 to 1 (see also Killeen, 1985). Epstein (1981) found that the amount of food consumed is an increasing but decelerating function of the duration for which food is made available.…”
Section: Resultsmentioning
confidence: 99%
“…Examples that fall into the first category are the delay-reduction hypothesis of Fantino (1969,1977,1981) and the incentive models of Killeen (1982Killeen ( , 1985. Models based on optimization have been proposed by Staddon (1983) and Fantino and Abarca (1985).…”
mentioning
confidence: 99%
“…The function u(v) is typically concave (e.g., Killeen, 1985): 16 pellets are less than twice as reinforcing as 8 pellets. Equation 7 is a multiplicative, not additive model, however, therefore no magnitude effect is predicted-or found .…”
Section: Rat Economicsmentioning
confidence: 99%
“…Satiation and warm-up effects can be substantial, and the mechanics of behavior provides a framework within which to derive models of them. Both the presentation of incentives and their removal often affect animals only after a lag; thus, we have warm-up effects when sessions start, cool-down or extinction effects when incentives cease, and responding through satiation in well-practiced The second, third, and nth instants of consumption are not contiguous with the response that brought them about; they are separated from it by n -1 prior instants of consumption (Killeen, 1985) that block their effectiveness. The last instants of a long-duration reward constitute a delayed reward.…”
Section: Economic Translationmentioning
confidence: 99%